Working capacity level defines the specific impairment profile of the comprehensive ICF core set for multiple sclerosis - Daiva Valadkevičienė; Irena Žukauskaitė; Indre Bileviciute-Ljungar; Rasa Kizlaitienė; Dalius Jatužis; Virginija Danylaitė Karrenbauer (Scientific Reports)
Abstract Multiple sclerosis (MS) unfavorably affects working capacity. The Comprehensive International Classification of Functioning, Disability and Health Core Set for MS (cICF-MS), issued by the World Health Organization, has not yet been extended to evaluate working capacity level (WCL). To evaluate the relative importance of cICF-MS categories in relation to WCL. Persons with MS (PwMS), N = 129, who had been referred to Lithuania’s Disability and Working Capacity Assessment Office for WCL determination, were divided into three groups according to the percentage of remaining WCL (WCL1 had 0–25%, WCL2 had 30–40%, and WCL3 had 45–55%). Data regarding the cICF-MS categories were collected through telephone interviews and patient documentation. Using the fractional ranking method, the mean values of cICF-MS impairment were ranked from the most severely affected to the least affected (rank 1–93). Ranks with the 10 highest mean values of impairment severity in each WCL group were included in a descriptive analysis. In the WCL1 and WCL2 groups, the most-affected cICF-MS categories reflected disability related to gait and motor function. The WCL3 group presented with pain, fatigue, and impairments to visual acuity, psychic stability, urination, and memory. This study has identified specific cICF-MS impairment profiles based on remaining WCL.